Question
Sun January 30, 2011 By: Shambhavi Sampath

i have a doubt in the first principle. y cant -- lim sin(x+h)-sinx / h h-0 be = sinx+sinh-sinx / h which will be equal to sinh / h = 1 i know this is wrong but please tell me the right reason why its wrong.

Expert Reply
Mon January 31, 2011
Dear Student
In the step sin(x+h)-sinx / h  cannot be  = sinx+sinh-sinx / h  since sin (A+B) = sin Acos B +cosA sin B and not sin A+Sin B .
Hope it clarifies your doubt
Regards'
Team Topperlearning
Ask the Expert